2016
DOI: 10.1144/m46.183
|View full text |Cite
|
Sign up to set email alerts
|

The variety and distribution of submarine glacial landforms and implications for ice-sheet reconstruction

Abstract: Glacimarine processes affect about 20% of the global ocean today, and this area expanded considerably under cyclical full-glacial conditions during the Quaternary (Fig. 1) . Many of the submarine landforms produced at the base and margin of past ice sheets remain well preserved on the seafloor in fjords and on high-latitude continental shelves after the retreat of the ice that produced them. These glacial landforms, protected from subaerial erosion and beneath wave-base and tidal currents in water that is oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 313 publications
(362 reference statements)
2
81
0
Order By: Relevance
“…Lidar data from Whidbey Island reveal that these features possess foreset slopes of 4-10°, exhibit sinuous topset-foreset crestlines, and are overprinted by lineations noted above (Figure 4). These features are tentatively interpreted as GZWs, given the strong geomorphological resemblance to known GZWs (Ottesen et al, 2005;Dowdeswell et al, 2016;Halberstadt et al, 2016;Simkins et al, 2016Simkins et al, , 2017b and internal stratigraphic architecture which reflects grounding zone processes, to be discussed in detail in later sections. These features are tentatively interpreted as GZWs, given the strong geomorphological resemblance to known GZWs (Ottesen et al, 2005;Dowdeswell et al, 2016;Halberstadt et al, 2016;Simkins et al, 2016Simkins et al, , 2017b and internal stratigraphic architecture which reflects grounding zone processes, to be discussed in detail in later sections.…”
Section: Resultsmentioning
confidence: 93%
“…Lidar data from Whidbey Island reveal that these features possess foreset slopes of 4-10°, exhibit sinuous topset-foreset crestlines, and are overprinted by lineations noted above (Figure 4). These features are tentatively interpreted as GZWs, given the strong geomorphological resemblance to known GZWs (Ottesen et al, 2005;Dowdeswell et al, 2016;Halberstadt et al, 2016;Simkins et al, 2016Simkins et al, , 2017b and internal stratigraphic architecture which reflects grounding zone processes, to be discussed in detail in later sections. These features are tentatively interpreted as GZWs, given the strong geomorphological resemblance to known GZWs (Ottesen et al, 2005;Dowdeswell et al, 2016;Halberstadt et al, 2016;Simkins et al, 2016Simkins et al, , 2017b and internal stratigraphic architecture which reflects grounding zone processes, to be discussed in detail in later sections.…”
Section: Resultsmentioning
confidence: 93%
“…The acoustic stratigraphy and morphology of the continental slope seaward of the grounding line deposits is typical of TMF sediments described on other high-latitude continental margins (Ó Cofaigh et al, 2003;Dowdeswell et al, 2016;Batchelor and Dowdeswell, 2014). The laterally discontinuous lenses of acoustically transparent material are glacio-genic debris flows and are interspersed with segments of acoustically laminated sediments, deposited when the ice stream retreated from the shelf edge.…”
Section: Trough Mouth Fanmentioning
confidence: 85%
“…3). TMFs commonly approach areas of 10 3 -10 5 km 2 and are most pronounced on shallow continental slopes (< 4 ‱ ) (Ó Cofaigh et al, 2003;Dowdeswell et al, 2016). The TMF in front of the De Long Trough has an average slope angle of 1.2 ‱ and is steeper above 1300 m b.s.l.…”
Section: Trough Mouth Fanmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphologically, these SRs (Figures a and ) appear similar to eskers, whose origin is related to glacial landforms (Burr et al, ; Lefort et al, ). Further, some terrestrial eskers have been reported with fan‐shaped deposits or outwash fans (Chandler et al, ; Dowdeswell et al, ; Gorrell & Shaw, ). In this regard, we examined their glacial association and found that (1) Reuyl is located in the near‐equatorial region, where the probability of glacial features is low.…”
Section: Description and Analysismentioning
confidence: 99%